Family Involvement in Firm’s Management and Productivity: An Empirical Evidence from Indonesia - Eko Suyono (University of Merdeka Malang, 2018)
This study aims to investigate the effect of family ownership on productivity, the difference on the productivity level between family managers and professional managers, and to evaluate whether family firm better to hire professional managers or family managers. Implementing purposive method on 535 companies listed on The Indonesian Stock Exchange in sampling technique, this study ended-up with 144 listed companies as a sample for five years (2011-2015), thus totally there are 720 company year observations. Then, this study uses OLS regression to test the hypotheses. The findings show that family ownership affects negatively on firm productivity which is measured by Standard Cobb-Douglas production function. Moreover, family managers are less productive than professional managers, therefore, this study recommends the family firm hire professional managers in order to improve firm productivity. To the best of my knowledge, it is the first study which relates the family ownership and firm productivity in Indonesia, thus it will be beneficial in knowledge development in this research field.JEL Classification: G32; M41 DOI: https://doi.org/10.26905/jkdp.v22i2.1587